Eines Tages werden wir wiederkommen, alle zusammen... .Aus der Serie: Wandmalereien in Sardinien 1968-1978 (D1/561-570) - Apitzsch, Thomas,
Eines Tages werden wir wiederkommen, alle zusammen... .Aus der Serie: Wandmalereien in Sardinien 1968-1978 (D1/561-570).